IMPLEMENTASI PROGRAM KELUARGA HARAPAN TERHADAP PEMENUHAN HAK SOSIAL WARGA LANSIA MISKIN (STUDI DI KECAMATAN JEBRES KOTA SURAKARTA) - Hidayat, Barjo Wahyu; Nuryadi, Muhammad Hendri; Rusnaini, Rusnaini (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2019)
The purpose of this study is to (1) knowhow the implementation of PKH policies towards the fulfillment of social rights of poor elderly citizens. (2) to find out the factors that affect the implementation of PKH policies. This study used descriptive qualitative research. Sources of data used are informants, events or activities and documents. The sampling technique is purposive sampling. Techniques of the data collection and compilation of data were done by interviews, observation and document analysis. The researcher used data triangulation and triangulation methods to obtain valid data. While the techniques of analyzing the data using interactive models are: (1) data collection (2) data reduction (3) data presentation and (4) drawing conclusions. This research procedure follows the following steps: (1) pre-field, (2) field implementation, (3) field analysis, and (4) preparation of the research report. Based on the results of the research can be concluded that: (1) Implementation of PKH in the fulfillment of the social rights of poor elderly people in Jebres District has been run in accordance with the SOP in the PKH guidebook, These activities include: Targetting, Socialization, Grants, group meetings, assistance and commitment verification. (2) There are supporting and inhibiting factors in the implementation of PKH in Jebres Sub-district, Supporting Factors: Resources, Public Support, and Characteristics of implementing agents, while the constraining factors: Communication, Disposition. and goals. Keywords :Implementation of policy, Family Hope Program, social rights of poor elderly citizens